The impact of Shareholder Rights Directive II on the level and structure of CEO compensation - Nguyen Trong Tien Phan; Niklas Meyer (MAB)
Over the last decade, CEO pay has increased drastically. The Shareholder Rights Directive II (“SRD II”) enacted by the EU is considered one solution to reduce potentially excessive executive pay but its effectiveness is unclear. To this end, this study investigates the impact of SRD II on the level and structure of CEO compensation in German and Austrian firms, compared to Swiss firms that did not experience a change in compensation-related regulation. Findings reveal that SRD II is not effective in reducing executive pay levels but promotes the use of deferred pay.